Age-Group Differences in the Performance of Selected Tests of Physical Function and Association With Lower Extremity Strength. Issue 1 (January 2019) - Francis, Peter; Mc Cormack, William; Lyons, Mark; Jakeman, Philip
Abstract : Background and Purpose: It is not known whether short functional performance tests used in aging research are appropriate for use in healthy older adults. The purpose of this study was to investigate age-group differences (sixth decade vs seventh decade) in selected functional performance tests and the association between lower extremity strength and functional performance. Methods: One hundred fifty-nine (18.2% [n = 29] male) healthy older adults (mean (standard deviation) age 60.4 (5.3) years), adults were recruited from the University of Limerick Campus Community. Knee extensor (KE) peak torque (PT) was assessed from a maximal voluntary isometric contraction. Subsequently, participants completed 10-m maximal and habitual gait speed tests, 5 repetition and 30-second chair rise tests, and a 900-m gait speed test. Results and Discussion: There was no difference in 10-m gait speed between those in the sixth and seventh decades ( P > .05). Compared with the sixth decade, those in the seventh decade required an extra 39 seconds to complete 900 m, an extra 0.6 seconds to complete 5 chair rises and performed 2 fewer chair rises in a 30-second time period ( P < .05). All tests had a weak association with KE strength ( r = 0.226-0.360; P < .05), except for 900-m gait speed that had a moderate association ( r = −0.537; P < .001). Our findings suggest that gait speed tests of 10 m or less cannot detect age-related difference in functional capacity when used in healthy older adults. Conclusion: Extended physical performance tests should be used in aging research on healthy older adults.